(untitled) (Medico Legal Update, 2020)
Data collected by WHO from various countries found that in 2018, 47% of all under-five deaths occurred in the neonatal period. The study aimed to analyze variables related to neonatal death in urban Indonesia. The analysis utilizes secondary data from the 2017 Indonesia Demographic and Health Survey. With stratification and multistage random sampling, 17,265 women aged 15-49 years in urban areas with live births in the last 5 years were sampled. Data were analyzed using a Binary Logistic Regression test. The analysis found that the richest women were 0.602 times more likely to experience neonatal death than the poorest women in urban areas(OR 0.602; 95% CI 0.409-0.886). Primiparous women were 0.526 times more likely to experience neonatal death than grand-multiparous women in urban areas of Indonesia(OR 0.526; 95% CI 0.307-0.903). Multiparous women were 0.636 times more likely to experience neonatal death than grand-multiparous women in urban areas in Indonesia(OR 0.636; 95% CI 0.492-0.822). Women who have antental care visits ? 4 times have a 0.237 chance of experiencing neonatal death compared to women who have antental care visits <4 times in urban areas in Indonesia(OR 0.237; 95% CI 0.163-0.334). It was concluded that there are 3 variables that affect neonatal death in urban area in Indonesia, namely wealth status, parity, and antenatal care.